INDIGENOUS ENTREPRENEURIAL ORIENTATION AND ECONOMIC COMPETITIVENESS OF MICRO-BUSINESSES IN EBONYI STATE - Okorie, Ebere Florence; Chiekezie, Obianuju Mary; Okafor, Lawrence Chima; Elikwu, Michael I; Nzewi, Hope Ngozi (EBSU Journal of Social Sciences and Humanities, 2024)
This study determined the relationship between indigenous entrepreneurial orientation and economic competitiveness of micro-businesses with a focus on the nature of the relationship between knowledge adaptability component of indigenous entrepreneurial orientation and value creation as well as customer services variables of business economic competitiveness. A resource-based theory of the firm was adopted because it is believed that through the use of the various resources (capital, human, social, information, and thought (orientation) at the disposal of the entrepreneur desired results are achieved. Data were generated using a questionnaire administered to the respondents selected through the judgmental (Purposive) sampling technique. Analysis was done via Statistical Package for Social Sciences (SPSS), version 25 to generate the data frequency, percentages, standard deviation, and means while hypotheses were tested using Pearson’s Product Moment Correlation Coefficient. The study found a significant positive relationship between knowledge adaptability and value creation/customer services. Based on the findings it was concluded that trying to replicate the successes of global markets using Eurocentric orientations might not be feasible as contextual nuances affect businesses vis a viz their sustainability, growth, and success; hence adoption of indigenous entrepreneurial orientations. The study recommended that indigenous entrepreneurs’ attention be focused on contextual peculiarities in their business environments to enable them to practice needful/appropriate ideologies to survive and remain economically competitive. It was also recommended that Nigerian indigenous entrepreneurs adopt, develop, and practice contextualized ideologies like knowledge and adaptability as they were found to enhance business competitiveness as well as sustainability; more so, these attributes can be utilized alongside already existing orientations adopted and found useful.